USING CLASSROOM LANGUAGE DURING THE LESSON - Suponova Durdona; Xudoyberdiyeva Maknuna (TADQIQOTLAR.UZ, 2023)
In a school room setting, superb conversation plays a fundamental position in facilitating gaining knowledge of and retaining an attractive environment. Teachers who master the art of the use of fabulous and superb language at some point of classes can significantly decorate scholar understanding, participation, and overall educational performance. This article explores key strategies and methods for using classroom language correctly to maximize the getting to know experience. The find out about investigated how scholar tutors of Big Buddies Club, a neighborhood provider tutoring English to elementary school students, discovered and used school room language in the prep training and tutoring program.